PENGARUH KUALITAS JASA “JENIUS BTPN” TERHADAP KEPUASAN NASABAH PADA PT. BANK TABUNGAN PENSIUN NASIONAL CABANG MAKASSAR - Dirwan Dirwan (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2018)
This research aims to know the influence of the quality of service by using four variables i.e. efficiency (X 1), fulfillment (X 2), reliability (X 3) and privacy (X 4) toward customer satisfaction at PT. Bank Branch National retirement savings Makassar. The data used are the primary data and secondary data with measurement tools using the method of multiple linear regression, hypothesis testing (t-test and F-test), as well as a test of the feasibility study (test reliability and validity of test) and the number of samples used as many as 100 respondents. The results of this study demonstrate a significant influence of partially and simultaneous to quality services are fulfillment, efficiency, reliability, and customer satisfaction against privacy. The most dominant variables influencing customer satisfaction is reliability.